+0  
 
+1
299
1
avatar+598 

Simplify \((i+1)^{3200}-(i-1)^{3200}\)

michaelcai  Dec 12, 2017
 #1
avatar+87699 
+1

( i + 1)3200  -  ( i - 1)3200   =

 

[ ( 1 + i)2]1600 - [ ( 1 - i)2]1600  = 

 

[  1 + 2i + i2 ] 1600 -  [ 1 - 2i + i2 ]1600   =

 

[ 1 + 2i - 1 ] 1600  -  [ 1 -2i - 1] 1600   =

 

[ 2i ]1600 - [  (-1) 2i ] 1600  =        {   (-1)2n  = 1   }

 

[2i]1600  -  [ 2i ] 1600   =

 

0

 

 

cool cool cool

CPhill  Dec 12, 2017
edited by CPhill  Dec 12, 2017

26 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.